Strategi Pengembangan Pelayanan Publik dalam Meningkatkan Transparansi Penyaluran Bantuan di Kabupaten Wajo - Amrizal Akmul; Sumarno Sumarno; Darmawan Darmawan; Andi Supriadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
According to Articles 33 & 34 of the 1945 Constitution Law of the Republic of Indonesia, the state is tasked with protecting the entire Indonesia nation and promoting general welfare in realizing social justice for all Indonesia people. One of the government's strategies in realizing social welfare is to distribute social assistance (Law Number 11 of 2009). Based on the Regulation of the Minister of Finance (PMK) number 181 of 2012, social assistance (bansos) is assistance in the form of transfer of money, goods, or services by the central/regional government to the community to protect the community from the possibility of social losses, increase economic capabilities, and improve social welfare. This type of research is descriptive qualitative research. This research is to identify and analyze Public Service Development Strategies in Increasing Transparency of Aid Distribution in Wajo Regency. This study uses qualitative research methods in the research design. The results of interviews with Social Service employees and the community show that the public service development strategy in Wajo Regency focuses on the use of information technology, effective socialization, and an empathetic approach. Overall, the efforts made by the Social Service have brought positive changes in the distribution of social assistance in Wajo Regency, with an increase in public trust and satisfaction with the services provided.